Pacific Island Economies - Browne, Christopher (International Monetary Fund, 2006)
The Pacific island region has considerable potential for development, especially in the areas of tourism, fisheries, forestry, mining, and agriculture. However, these countries face many challenges to developing their economies and raising living standards, including their small size, distance from major markets, and vulnerability to natural disasters. The first half of this book provides an assessment of regional issues. The second half includes country-specific chapters, which provide an overview of each countries economic performance since independence and the main challenges ahead.